PEMANFATAAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) UNTUK PENENTUAN JENIS BARANG YANG AKAN DI PRODUKSI - Hartono, Hartono (UNIVED Press, 2013)
Analytical Hierarchy Process ( AHP ) is often used in support of decision-making, decision-making when it faced a number of criteria and a number of alternative. Where the existing criteria in the decision-making certainly has a number of alternative weighting. One of the problem areas that can be solved by the AHP method is the determination of the production of a product. Where the criteria in question is composed of the following criteria: availability of raw materials, production time , production cost, and profit margin. Sometimes problems regarding the items that will be produced is important with regard to the limited capacity of the company's resources such as labor, machinery production , and so on. These criteria will be determined local weights, with alternative consists of each of the existing products. Having determined the weight of each criterion, then the next step is to set the weight of each alternative for each criterion in order to obtain a global weight. This assessment is important to determine which products will be produced. Keywords: Analytical Hierarchy Process, local weight, global weight